Pancasila as a Political Ethic - Abigail Ahmad Taufiq; Anisa Fisa Bilhillah; Nabilla Yogy Irawan; Riska Andi Fitriono (CV. Rayyan Dwi Bharata, 2022)
Pancasila and Citizenship Education (PPKn) is strategic in the introduction and penetration of democratic principles, the spirit of nationalism, participation in the development of the country and character, schools through civic education in schools, and the wider community (community citizenship). Political education is part of the formation of concepts and conditions for building civil society, including the rights and responsibilities of citizenship that sustain the democratic life of a democratic state. The political competence of citizens must be accompanied by supporting ethics as the disposition or character of the development of previous competencies (knowledge and competence). The concept of ethics as a guideline and action in carrying out the democratic life of the Indonesian nation also contributes to this. Positioning in line with ethics and the concept of Pancasila as a view of life and philosophy in society, nation, and state.